PERBEDAAN KENYAMANAN PENGGUNAAN KACAMATA DAN LENSA KONTAK PADA ALUMNI ANGKATAN 15 PONDOK PESANTREN AL KAUTSAR BANJAR - Fauziah, Fatiah Nurul; Maryani, Febri; Doringin , Ferry; Habiba, Putri Ghanim Septia; Abdilah, Bunyamin Rizki (Jurnal Mata Optik, 2025)
This study aims to determine the difference in comfort between the use of glasses and contact lenses in alumni ofthe 15th batch of Al-KautsarIslamic Boarding School Banjar.The focus of the research is directed atthe subjectiveexperience of users in daily activities involving physical, psychological, and social aspects. The research methodused was descriptive qualitative with a semi-structured interview technique conducted through telephone mediawith three informants who were selected purposively because they had experience using both visual aidsalternately in daily life. Data were analyzed through the preparation of interview guidelines, recording,transcripts, interpretation, and drawing conclusions. The results show that contact lenses are preferred becausethey provide visual comfort and support aesthetics, but are at risk of irritation if not properly maintained. Incontrast, glasses are considered safer, practical, and easier to maintain, but they can put physical strain on thenose and ears. The use of visual aids is situational and adaptive, depending on visual comfort, environment, andsocial needs. These findingsreflect Kolcaba's theory of comfort, with dimensions of relief, ease, and transcendenceseen in physical, psychospiritual, environmental, and social contexts.